Research data for: Optimized shapes of magnetic arrays for drug targeting applications - Barnsley, L; Carugo, D (University of Oxford, 2016)
The .opj files can be opened using Origin (OriginLab, MA, USA). The file, "Volume dep study.opj" contains designs, data and analysis of optimized magnet arrays reported or referred to in the related publication, specifically in section 3.1. The file "POI dep study.opj" contains designs, data and analysis of optimized magnet arrays reported or referred to in the related publication, specifically in sections 3.2 and 3.5. The file "DOF dep study.opj" contains designs, data and analysis of optimized magnet arrays reported or referred to in the related publication, specifically in sections 3.3 and 3.6.